Методи протидії несанкціонованого доступу - Світличний, М. С. (ХНУРЕ, 2023)
Unmanned aerial vehicles (UAVs) typically carry sensitive data and equipment that may be at risk of unauthorized access or hacking. Unauthorized access countermeasures in UAVs include technical and procedural measures that help ensure security and protection against such attacks. Among the technical measures, one can note the encryption of data transmitted and stored on the UAV and the use of network protocols with security. Procedural measures include ensuring the physical security of the UAV, prohibiting access to equipment without appropriate authorization, and controlling the activities of personnel who have access to the UAV